2023
DOI: 10.1002/bies.202200220
|View full text |Cite
|
Sign up to set email alerts
|

Fraternity of old‐timers: How ubiquitin regulates miRNA functions

Abstract: miRNA‐mediated gene repression and ubiquitin‐dependent processes are among the oldest and most versatile mechanisms that control multiple molecular pathways, rather than just protein turnover. These systems were discovered decades ago and have become among the most studied. All systems within cells are interconnected, and these two are no exception: the plethora of studies have demonstrated that the activity of the miRNAs system depends on players of the ubiquitin‐centered universe of processes, and vice versa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…One may suggest that the possible functions of the Dora-mediated ubiquitination and proteolysis of Ago1 is the elimination of such locked and nonfunctional Ago1 engaged with TDMD target from the cellular pool. This would make TDMD complementary to the mechanism of the control of quantity and quality of the unloaded Ago (Ryazansky and Akulenko 2023). If so, the knock-out of Dora should reduce the fraction of the functionally active Ago1 and derepress miRNA targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may suggest that the possible functions of the Dora-mediated ubiquitination and proteolysis of Ago1 is the elimination of such locked and nonfunctional Ago1 engaged with TDMD target from the cellular pool. This would make TDMD complementary to the mechanism of the control of quantity and quality of the unloaded Ago (Ryazansky and Akulenko 2023). If so, the knock-out of Dora should reduce the fraction of the functionally active Ago1 and derepress miRNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…In S2 cell culture Dora is able to recognize only Ago1-bound miRNAs, but not Ago2-bound small RNAs mostly belonging to endo-siRNAs (Kingston et al 2022). The bioinformatic search revealed that SWIM8 orthologs are encoded in the genomes of animals, but not in Protozoa, plants, or fungi (Ryazansky and Akulenko 2023). So, the targeted degradation of miRNAs mediated by ZSWIM8 homologs seems to be widely distributed across Metazoa species.…”
Section: Introductionmentioning
confidence: 99%